Eksistensi video game streaming dalam industri gaming Indonesia - Hidayanto, Syahrul (Faculty of Communications Science, Dr. Soetomo University, 2020)
This research explored the motivation and satisfaction of gamers in watching streaming video games and the impact of streaming video games on the growth of the gaming industry in Indonesia. The research approach was qualitative method with a case study research strategy. Based on the results of data analysis obtained from in-depth interviews with five informants who met the criteria as gamers and professional streamers, it was understood that interpersonal utility motives, seeking information, and entertainment became the main motives for gamers in watching video games streaming. Then, the YouTube gaming platform was more preferred by professional gamers in Indonesia than Twitch. Finally, video games streaming on the gaming industry in Indonesia affects the decision to buy games, ways to sell games, bringing classic games back, and the success of independent game developers.